The economic burden of obesity in 2024: a cost analysis using the value of a statistical life - Nadia J. Sweis (Critical Public Health)
In 2024, the economic burden of obesity remains a paramount global concern due to its escalating prevalence, which imposes substantial pressures on healthcare systems, hampers productivity, and detracts from the quality of life. This paper explores the evolving obesity epidemic and its economic ramifications, emphasizing the necessity of precise measurement techniques to inform policy development and resource allocation. The study adopts the Value of a Statistical Life (VSL) methodology, which provides an innovative approach to quantifying the monetary value of mortality risk reductions associated with obesity-related health conditions. This approach surpasses traditional cost analyses that focus on direct medical expenses by incorporating a willingness-to-pay metric, reflecting societal preferences for risk mitigation. Our findings present a comprehensive cost analysis for the year 2024, utilizing both total deaths and Disability-Adjusted Life Years (DALYs) within the VSL framework, highlighting the importance of such an approach in understanding the full economic impact of obesity on a global scale.